Investor-State Arbitration and Domestic Environmental Protection - Tamara L. Slater (Washington University Global Studies Law Review, 2015)
Environmentalists and advocates of free trade have begun to agree that disputes arising under international trade and investment agreements raise not only commercial issues, but also important questions of public policy. This Note explores whether and how a country can protect the environment through domestic laws given the frequency with which a provision requiring Investor-State Dispute Settlement (ISDS), a particular dispute resolution mechanism, is included in investment agreements and subsequently utilized by corporations.
Keywords: climate change; environment; trade; ISDS; Investor-State; pollution; arbitration; TTP; Trans-Pacific Partnership